En bloc resection of huge primary tumors with epidural involvement in the mobile spine using the “rotation–reversion” technique: Feasibility, safety, and clinical outcome of 11 cases - Lu, Ming; Zhou, Zhongxin; Chen, Wei; Lei, Zixiong; Dai, Shuangwu; Hou, Changhe; Du, Shaohua; Jin, Qinglin; Jin, Dadi; Boriani, Stefano; Li, Haomiao (Frontiers in Oncology, 2022)
Background: En bloc resection of spinal tumors provides better local control and survival outcomes than intralesional resection. Safe margins during en bloc resection of primary spinal tumors with epidural involvement are required for improved outcomes. The present study describes a “Rotation-Reversion” technique that has been used for en bloc resection of huge primary tumors in the mobile spine with epidural involvement, as well as reporting the clinical outcomes in these patients. Methods: All patients with primary spine tumors who were treated with the Rotation-Reversion technique at our institution between 2015 and 2021 were evaluated retrospectively. Of the patients identified, those with both huge extraosseous soft tissue masses and epidural involvement were selected for case review. Clinical and radiological characteristics, pathologic findings, operative procedures, complications, and oncological and functional outcomes of these patients were reviewed. Results: Of the 86 patients identified with primary spine tumor who underwent en bloc resection using the Rotation-Reversion technique between 2015 and 2021, 11 had huge extraosseous soft tissue masses with epidural involvement in the mobile spine. The average maximum size of these 11 tumors was 8.1 × 7.5 × 9.7 cm. Median follow-up time was 28.1 months, mean operation time was 849.1 min (range 465–1340 min) and mean blood loss was 6972.7 mL (range 2500–17700 mL), with 10 (91%) of the 11 patients experiencing perioperative complications. The negative margin rate was 91%, with only one patient (9%) experiencing local recurrence. Ten patients were able to walk normally or with a crutch at last follow-up, whereas one was completely paralyzed preoperatively. Conclusion: The Rotation-Reversion technique is an effective procedure for the en bloc resection of huge primary spinal tumors, with the extension of invasion in selected patients including not only the vertebral body but also the pedicle and part of the posterior arch.